PENGARUH PEMASARAN MEDIA SOSIAL DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA TOKO TIGER WILD STORE - Kurniawan, Andri; Noor, M. Arief; Sutrisno, Hadi; Hakim , Melati Puspita (Jurnal Ilmiah Ekonomi Manajemen & Bisnis, 2023)
This study examines the influence of social media marketing and service quality on consumer purchasing decisions at Tiger Wild Store. Against the background of the increasing use of the internet and social media, this study highlights the significant role of social media such as Instagram, Facebook, and others in product promotion. In addition, the quality of service received by consumers also affects purchasing decisions. This study uses a quantitative descriptive method with a population of all Tiger Wild Store consumers and a sample of 50 respondents. Data were collected through questionnaires and analyzed using a Likert scale, validity, and reliability tests. The results showed a significant influence between social media marketing and service quality on consumer purchasing decisions. These findings provide insight for companies to improve marketing and service strategies to increase sales.